2009
DOI: 10.1080/00207450902841723
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Complications of Diabetes in Streptozotocin-Induced Diabetic Rats: A Histopathological and Immunohistochemical Examination

Abstract: Diabetes mellitus is a common, potentially serious metabolic disorder. Over the long term, diabetes leads to serious consequences in a number of tissues, especially those that are insulin insensitive (retina, neurons, kidneys). It also causes a variety of functional and structural disorders in the central and peripheral nervous systems. We investigated whether neurodegenerative changes were observable in the hippocampus, cortex, and cerebellum after 4 weeks of streptozotocin (STZ)-induced diabetes in rats and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…The cerebellar cortex was susceptible to hyperglycemia-induced oxidative stress, which contributed to the neuronal damage and increased astrocyte activity (8). Immunohistochemical studies that evaluated the effects of STZ-induced diabetes on the nervous system of rats with 6 weeks or longer duration of diabetes have shown significant increases in the GFAP and S-100b constituents in diabetics compared to nondiabetic controls (1). Diabetes was shown to cause increased glial activity and the mechanism was thought to be elevated oxidative stress, whereas these histopathological and immunohistochemical changes could not be observed in STZ-induced diabetic rats after 4 weeks (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellar cortex was susceptible to hyperglycemia-induced oxidative stress, which contributed to the neuronal damage and increased astrocyte activity (8). Immunohistochemical studies that evaluated the effects of STZ-induced diabetes on the nervous system of rats with 6 weeks or longer duration of diabetes have shown significant increases in the GFAP and S-100b constituents in diabetics compared to nondiabetic controls (1). Diabetes was shown to cause increased glial activity and the mechanism was thought to be elevated oxidative stress, whereas these histopathological and immunohistochemical changes could not be observed in STZ-induced diabetic rats after 4 weeks (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, all these studies are not specific to the cerebellum. Research studies related to the cerebellum are very few to our knowledge (1,2,4,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive and behavioral dysfunctions are being the most apparent CNS impairments reported in both humans (Petrofsky et al, 2005; Kodl and Seaquist, 2008) and animal models of diabetes (Biessels et al, 1994; Coleman et al, 2004; Guven et al, 2009). It is held that altered metabolism of lipids, proteins and carbohydrates following diabetes leads to oxidative stress and cell death in the brain, causing a state of dysfunctions in cognition and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have shown that diabetes causes a variety of functional and morphological disorders in the central nervous system (including hippocampus, cortex, and cerebellum) (Biessels et al, 1999;Selvarajah & Tesfaye, 2006;Mooradian, 1997a;Mooradian, 1997b;Guven et al, 2009), the role of the central neural component in the blunted arterial baroreflex in type 1 diabetes is less well documented. One recent study from Gu, et al (Gu et al, 2008) suggests that a deficit of the central neural component contributes to the attenuation of arterial baroreflex in OVE26 type 1 diabetic mice.…”
Section: Involvement Of the Central Neural Component In The Blunted Amentioning
confidence: 99%